A Study on Electric Dryer for Cash Crops Drying as an End-Use Promotion of Micro Hydro Power in Nepal & Its Comparative Analysis with Biomass Based Drying System - Gyanwali, K.; Aryal, P.; Adhikari, B. (Kathmandu University Journal of Science, Engineering and Technology, 2014)
Electric dryers serve farmers as an efficient, environment friendly, and proper technology with high performance for quality product drying than other types of conventional dryers. Development and implementation of electric dryers have become a must to bring socio-economic and technological change in rural Nepal. For performance testing and comparison with biomass-based drying systems, an electric dryer was designed and locally fabricated, taking special care in insulation of the system and transported to Baletaksar-5, Gulmi. Performance testing was followed by individual parts testing with the observation of drying pattern. Two different performance tests were carried out with 25 kg of fresh ginger as input, which was dried for 4.5 hours. The first test was 30% efficient, consuming 40 kWh of electric power with an output of 5.4 kg of dried ginger. When leakage of the hot and dry air from the dryer was minimized in the second test, the dryer was 37% efficient. Later on, the electric dryer system was compared with a biomass-based dryer system, which shows that the drying rate of the electric dryer is stable and constant, also the required temperature in this system can be maintained as per requirement like 60°C in the case of ginger drying. The temperature profile of drying air in the biomass-based system was unstable and inconsistent with periodical variation like a sinusoidal curve. The efficiency of the electrical dryer was much higher compared to the biomass-based system, which lies between 10 to 13% depending upon feedstock input for gasifier. Financial analysis was performed, which shows an annual revenue of NRs. 2,340,000 with a total breakeven sales of 4379.5 kg dry ginger and corresponding payback period is 0.9357 years.